The Effect of Curcumin Supplementation on Irisin, Nesfatin-1, and Leptin Levels in Rats Subjected to Long-Term Treadmill Exercise - Delioglan, A; Pancar, Z; Darendeli, MK; Kilicoglu, Y; Ulusal, H; Dal, M; Tasdogan, AM; Yan, X (My University, 2025)
Background. Curcumin supports metabolism with its antioxidant and anti-inflammatory effects. It is particularly effective in reducing metabolic stress caused by prolonged exercise. Objectives. This study aimed to investigate the impact of curcumin supplementation on Irisin, Nesfatin-1, and Leptin hormone levels in rats undergoing prolonged treadmill exercise. Methods. A total of 32 male Wistar-Albino rats were divided randomly into four equal groups: The control group (n=8), the curcumin group (n=8), the treadmill group (n=8), and the curcumin+treadmill group. The experiment lasted eight weeks, with one week of treadmill acclimatization. No intervention was applied to the control group. Curcumin was given at 200 mg/kg, and treadmill exercise was performed for 30 min at 45 cm/s, three days weekly. The Curcumin+Treadmill group was fed 200 mg/kg/day and performed three days a week for 30 minutes at an average speed of 45 cm/s. After the study, rats were euthanized, and blood samples were collected for analysis. Irisin, nesfatin-1, and leptin hormone levels were determined using the ELISA method. Results. Our study showed a significant increase in irisin levels in both the curcumin and exercise groups compared to the control group. For nesfatin-1, levels were significantly decreased in the curcumin group compared to the control, while they were significantly increased in the curcumin+exercise group. Leptin levels were the highest in the exercise group, showing a significant increase compared to the control group (p<0.05). In contrast, the leptin levels in the curcumin group were significantly lower than those in the exercise group. Conclusion. This study demonstrates that combining curcumin supplementation and exercise positively affects irisin, nesfatin-1, and leptin hormone levels, contributing to metabolic balance.
Keywords: Exercise; Supplementation; Leptin